2018
DOI: 10.3390/s18092920
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic EEG Microstates in Mental Rotation

Abstract: Mental rotation is generally analyzed based on event-related potential (ERP) in a time domain with several characteristic electrodes, but neglects the whole spatial-temporal brain pattern in the cognitive process which may reflect the underlying cognitive mechanism. In this paper, we mainly proposed an approach based on microstates to examine the encoding of mental rotation from the spatial-temporal changes of EEG signals. In particular, we collected EEG data from 11 healthy subjects in a mental rotation cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…This anterior localization, together with the relatively late occurrence of Map 8, is compatible with decision processes related to response selection ( Seepanomwan et al, 2015 ). This interpretation is supported by previous studies which have similarly identified late electrophysiological components occurring after the spatial transformations during MR ( Overney et al, 2005 ; Kong et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…This anterior localization, together with the relatively late occurrence of Map 8, is compatible with decision processes related to response selection ( Seepanomwan et al, 2015 ). This interpretation is supported by previous studies which have similarly identified late electrophysiological components occurring after the spatial transformations during MR ( Overney et al, 2005 ; Kong et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…This anterior localization, together with the relatively late occurrence of Map 8, is compatible with decision processes related to response selection 52 . This interpretation is supported by previous studies which have similarly identified late electrophysiological components occurring after the spatial transformations during MR 53,54 .…”
Section: Discussionsupporting
confidence: 87%
“…As artificially delaying a response may invoke processes unrelated to the decision [ 45 ], novel algorithms processing EEG signals which deal with varying epoch sizes may be as beneficial. Finally, comparing different time windows (e.g., initial 500 vs last 500 ms) informed by EEG microstate analysis may reveal how spectral and spatial EEG features differ between stages of cognitive processing (e.g., encoding of visual information, mental rotation, and decision making) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the application of SPoC to extract spatial filters required epochs of equal size, we exclusively kept the initial 500 ms from each epoch (i.e., from 0 to 500 ms) and removed epochs with less data available. We chose the initial 500 over the last 500 ms per epoch as EEG microstates indicate that the initial period contains processes related to the encoding of visual information and mentally rotating an object [ 39 ]. After removing on average 15.3% of epochs with 3D figures presented due to missing or too early responses, this procedure yielded on average across all participants 163 epochs (min = 105, max = 186 epochs) with 500 x 32 samples per epoch.…”
Section: Methodsmentioning
confidence: 99%